Impact of Flood on Performance of Students The Case of Secondary School Students in Jaleshwor Municipality, Mahottari - Chaudhary, Gangadhar; Timsina, Tatwa P. (Journal of Advanced Academic Research, 2018)
School buildings are vulnerable towards natural disaster in Nepal and many of them are poorly constructed, old and situated on the marginal lands. The school buildings and communities are always flooded with water during rainy season, which threaten the academic performance of the students. The study aimed to assess the perception of school students on the potential effects of floods on the school infrastructures, the students’ residents, community infrastructures and overall impacts on their academic performance. The mixed method was used to collect the data and analyzed with the use of simple statistical tools. The well-structured questionnaires were distributed to 100 students of three schools in Jaleshwor municipality in Mahottari district of Nepal. The result of this research showed that flood impacts directly to the performance of the students mainly of secondary level. They were in fear of any upcoming disastrous events like the collapse of infrastructures in school as well as their residence. The study revealed high levels of vulnerability to the impact of floods, reduce the quality of education that disrupt the access of the rights of the education to the students. The research identified that during the flood disaster, the public properties as well as private properties are suffering more. The study recommends familiarizing and giving disaster education to the school students so that they adopt the effects of natural disaster. Operation of the education in good infrastructures ensures the quality education and makes the better performance of the students in overall.